Trichothecene genotype profiling of wheat Fusarium graminearum species complex in Paraguay - Arrua Alvarenga, Andrea Alejandra (2022)
Paraguay is a non-traditional wheat-producing country in one of the warmest regions in South America. Fusarium Head Blight (FHB) is a critical disease affecting this crop, caused by the Fusarium graminearum species complex (FGSC). A variety of these species produce trichothecenes, including deoxynivalenol (DON) and its acetylated forms (3-ADON and 15-ADON) or nivalenol (NIV). This study characterized the phylogenetic relationships, and chemotype diversity of 28 strains within FGSC collected from wheat fields across different country regions. Phylogenetic analysis based on the sequence of elongation factor-1α gene (EF-1α) from 28 strains revealed the presence of four species in the FGSC: F. graminearum sensu stricto, F. asiaticum, F. meridionale and F. cortaderiae. Ten strains selected for further analysis revealed that all F. graminearum strains were 15-ADON chemotype, while the two strains of F. meridionale and one strain of F. asiaticum were NIV chemotype. Thus, the 15-ADON chemotype of F. graminearum sensu stricto was predominant within the Fusarium strains isolated in the country. This work is the first report of phylogenetic relationships and chemotype diversity among Fusarium strains which will help understand the population diversity of this pathogen in Paraguay.